Pencirian Karbon Organik Air Sungai Citarum Hulu Dari Masukan Air Limbah Penduduk dan Industri - Harsono, Eko; Nomosatryo, Sulung (JURNAL BIOLOGI INDONESIA, 2010)
ABSTRACTCharacterisation of Organic Carbon of Up Stream Citarum River Water from Domestic andIndustrial Waste Effluent. The local government of Citarum upstream area has conducted theriver cleaning program to increase Disolved Oxygen since 1991 until now. The program hasimpacted to installments of to wastewater treatment for 80% industrials in the Upper Citarumdrainage area declining the load of BOD5 wastewater. However most of waste water comingfrom Banung population have been treated in the collective wastewater treatment (IPAL) ofBojongsoang. Nevertheless, the low concentration of Dissolved oxygen which is under theminimum stream standard concentration, 3mg/l still becomes a problem until now. Anineffectiveness of improvement of the DO is caused by the treatment effluent BOD5 load fromdomestic and industrial wastewater and low awareness industrial wastewater aboutcharacteristics of river water quality . This research aimed to characterize the BOD oxidationrate and BOD5 regime of each river reach base on wastewater domestic or industrial characteristic.The result of this research can then be applied to build the priority of the load reduction ofBOD5 wastewater domestic or industrial in each reach of that river. The characteristic ofoxidation rate have investigated at influent point and water body of Upper Citarum River bymultivariate cluster observation. The oxidation rate was calculated by least-square methodfrom BOD data. The BOD observation was measured by BOD meter everyday for 5 days. Theresult shows that Curugjompong at 0 to 21st km and 36th km to Majalaya bridge ischaracterizedby an industrial sewage, while the upper Citarum at 21 to 36 Km is characterizedby an domesticsewage.Key words: Characteristic, oxydation rate, Citarum river, organic carbon.